Secoisolariciresinol Diglucoside Exerts Anti-Inflammatory and Antiapoptotic Effects through Inhibiting the Akt/IκB/NF-κB Pathway on Human Umbilical Vein Endothelial Cells - Shaoyang Zhang; Meili Cheng; Zhen Wang; Yuzhi Liu; Yuhua Ren; Shikuo Rong; Xue Wang (Hindawi Limited, 2020)
Inflammation is a key regulator in the progression of atherosclerosis (AS) which extremely affects people's health. Secoisolariciresinol diglucoside (SDG), a plant lignan, is relevant to angiogenesis and cardioprotection against ischemia-reperfusion injury and improves vascular disorders. However, the effect of SDG on cardiovascular disorder is not clear. In the present study, we aimed to investigate the effects of SDG on lipopolysaccharide- (LPS-) stimulated Human Umbilical Vein Endothelial Cells (HUVECs) and elucidate the underlying mechanism. The LPS-stimulated HUVEC cellular model was established. The cell viability, the cell tube formation activity, the nitric oxide (NO) release, the levels of inflammatory cytokine interleukin-1β (IL-1β), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), the activation of nuclear factor kappa-B (NF-κB) pathway, and the expression of protein kinase B (Akt) were determined using Cell Counting Kit-8, cell tube-formation assay, western blotting, and enzyme-linked immunosorbent assay. Our results revealed that SDG reduces the angiogenic capacity of HUVECs and inhibited LPS-mediated HUVEC injury and apoptosis. In addition, SDG increased NO release and decreased the levels of IL-1β, IL-6, and TNF-α in LPS-treated HUVECs. Meanwhile, SDG inhibited the NF-κB pathway and downregulated Akt expression in LPS-induced HUVECs. Our results indicated that SDG relieves LPS-mediated HUVEC injury by inhibiting the NF-κB pathway which is partly dependent on the disruption of Akt activation. Therefore, SDG exerts its cytoprotective effects in the context of LPS-treated HUVECs via regulation of the Akt/IκB/NF-κB pathway and may be a potential treatment drug for cardiovascular disease.